Sirex Woodwasp Sirex noctilio Fabricius (Hymenoptera: Siricidae) - Demian Gomez; Andrea Lucky; Jiri Hulcr (EDIS)
Contents: Introduction - Distribution - Description - Biology - Hosts - Damage - Management - Selected References